Hand hygienization challenge for the implementation of the central venous cateter bundles - Thabata Coaglio Lucas; Poliana Lopes Campos de Sá; Laura Petronilha dos Santos; Cleyde Amaral Leite; Ana Luisa de Paulo Caldeira; Adriana Cristina de Oliveira (Universidade de Santa Cruz do Sul, 2018)
Background and objectives: In the prevention of adverse events associated with bloodstream infections, the hand Hygiene (HM) is one of the priority measures in actions aimed at patient safety. The objective was to verify the challenge for the implementation of bundles for the prevention of blood infection associated with the central venous catheter. Methods:Exploratory-descriptive quantitative cross-sectional study, performed at the intensive care unit of a philanthropic hospital in the interior of Minas Gerais. A multiprofessional team was directly observed by means of a data collection instrument that contained variables such as HM in medication administration, exchange of dressings and insertion of the catheter. Pearson's chi-square test was used when the expected value was> 5 and Fisher's exact test for the expected value